1986
DOI: 10.1088/0031-8949/33/2/016
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation State of Iron in SNC Meteorites as Studied by Mössbauer Spectroscopy

Abstract: Mössbauer investigations of three meteorites of the type SNC-achondrites are reported. The results are compared with Mössbauer spectra of other meteorites, and selected terrestrial and lunar rocks. Through the oxidation state of iron in the pyroxenes and magnetic oxides studied, the work confirms that the mantle of the Earth is highly oxidized compared with the mantle of asteroidal bodies and lunar basalts. The investigations show that at least one of the SNC meteorites (Nakhla) comes from a highly oxidized pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
1

Year Published

1989
1989
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 15 publications
1
16
1
Order By: Relevance
“…Perhaps the aliquot studied by Vieira et al was unusual in that it lacked titanomagentite. Vieira et al (1986) found only Fe 2+ pyroxene peaks in their paramagnetic fractions from Zagami.…”
Section: Previous Workmentioning
confidence: 93%
See 4 more Smart Citations
“…Perhaps the aliquot studied by Vieira et al was unusual in that it lacked titanomagentite. Vieira et al (1986) found only Fe 2+ pyroxene peaks in their paramagnetic fractions from Zagami.…”
Section: Previous Workmentioning
confidence: 93%
“…In a magnetic fraction separated from Nakhla, Vieira et al (1986) found magnetite, ilmenite, and ulvöspinel in small (unspecified) amounts. The Mössbauer spectrum from the paramagnetic fraction of Nakhla showed the presence of a small amount of Fe 3+ ; the amount was not specified by Vieira et al (1986), but the percentage of Fe 3+ in pyroxene was later estimated to be 2% (Vistisen et al 1990).…”
Section: Previous Workmentioning
confidence: 94%
See 3 more Smart Citations